2021
DOI: 10.3168/jds.2020-18702
|View full text |Cite
|
Sign up to set email alerts
|

Sheep milk kefir sweetened with different sugars: Sensory acceptance and consumer emotion profiling

Abstract: The objective of this study was to determine the sensory acceptance and emotional profile of sheep milk kefir sweetened with different sugars (demerara sugar, brown sugar, fructose, coconut sugar, and honey, 100 g/L). Consumers (n = 100) assessed sensory acceptance (appearance, aroma, taste, texture, and overall impression), and expressed their emotions (satisfied, active, loving, calm, comfortable, energetic, happy, healthy, refreshing, disgusted, worried, and upset). The emotions "satisfied," "active," "co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
0
13
1
1
Order By: Relevance
“…Kefir is produced from the fermentation of various animal milks such as cow, goat, sheep or buffalo and characterised by a distinct yeast‐like flavour that feels gaseous or foamy in the mouth (Mitra and Ghosh 2020; Larosa et al . 2021b). Kefir has a very complex taste since the grains used in its production have diverse and complex microbiota such as lactic acid bacteria ( Lactobacillus , Lactococcus , Streptococcus , Leuconostoc ), yeast and acetic acid bacteria (Farag et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kefir is produced from the fermentation of various animal milks such as cow, goat, sheep or buffalo and characterised by a distinct yeast‐like flavour that feels gaseous or foamy in the mouth (Mitra and Ghosh 2020; Larosa et al . 2021b). Kefir has a very complex taste since the grains used in its production have diverse and complex microbiota such as lactic acid bacteria ( Lactobacillus , Lactococcus , Streptococcus , Leuconostoc ), yeast and acetic acid bacteria (Farag et al .…”
Section: Introductionmentioning
confidence: 99%
“…2018; Larosa et al . 2021a, 2021b) and update on scientific data on positive health effects of its microbiota. Kefir is produced from the fermentation of various animal milks such as cow, goat, sheep or buffalo and characterised by a distinct yeast‐like flavour that feels gaseous or foamy in the mouth (Mitra and Ghosh 2020; Larosa et al .…”
Section: Introductionmentioning
confidence: 99%
“…According to Larosa et. al use of honey for kefir improves acceptance in appearance and aroma 46 . Păucean et al showed that the optimal addition of honey to kefir was 2.5% (w/v), and the introduction of 4% honey (w/v) made the kefir too sweet.…”
Section: Resultsmentioning
confidence: 99%
“…Scoring tests are the most common methods to reveal the sensory characteristics of a product in order to determine the consumer preference. In addition, there are new techniques such as free word association (Judacewski et al, 2019) or emotional profiling (Larosa et al, 2021b) that have been developed in recent years.…”
Section: Sensorial Propertiesmentioning
confidence: 99%